2015
DOI: 10.1590/2177-6709.20.5.050-057.oar
|View full text |Cite
|
Sign up to set email alerts
|

Influence of occlusal plane inclination and mandibular deviation on esthetics

Abstract: Objective: The aim of this study was to assess the degree of perception of occlusal plane inclination and mandibular deviation in facial esthetics, assessed by laypeople, dentists and orthodontists. Methods: A woman with 5.88° of inclination and 5.54 mm of mandibular deviation was selected and, based on her original photograph, four new images were created correcting the deviations and creating more symmetric faces and smiles. Examiners assessed the images by means of a questionnaire. Their opinions were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Some studies compared directly dentists vs laypersons, finding tolerances of 1 mm for dentists and 3 mm for laypersons, 19 others found similarities between both groups. 20,21 The present study found the threshold at 2 (or the equivalent of 1 mm 19 ), corroborating the results of Padwa et al, 22 showing a slightly higher sensitivity of the laypersons interviewed compared to the literature. It is evident that there is a high variability of results in the literature regarding was to see if the nose and chin inclinations affected the ratings considering which side of the cant was involved.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies compared directly dentists vs laypersons, finding tolerances of 1 mm for dentists and 3 mm for laypersons, 19 others found similarities between both groups. 20,21 The present study found the threshold at 2 (or the equivalent of 1 mm 19 ), corroborating the results of Padwa et al, 22 showing a slightly higher sensitivity of the laypersons interviewed compared to the literature. It is evident that there is a high variability of results in the literature regarding was to see if the nose and chin inclinations affected the ratings considering which side of the cant was involved.…”
Section: Discussionsupporting
confidence: 91%
“…Окклюзионная плоскость по отношению к франкфуртской горизонтали (Or-Po), проходящей от нижнего края орбиты до верхнего края наружного слухового прохода, располагается под углом 5,59±5,23˚. Ориентация окклюзионной плоскости устанавливается с учётом угла окклюзионной плоскости, который образуется франкфуртской горизонталью (Or-Po) и касательной, проходящей через бугорки нижних премоляров к выемкам между щёчными бугорками нижних вторых моляров [6]. В норме величина угла окклюзионной плоскости находится в пределах 8±4°.…”
Section: Abstract: Frankfurt Plane Occlusal Plane Physiological Occlusion Teleradiography Of the Head Types Of Jaw Growthunclassified
“…Of these, we have already discussed nose length. As for the inclination of the occlusal plane and the vertical position of the maxillary arch, these parameters are usually regarded as important determinants of smile esthetics [31][32][33]. Unfortunately, no studies are available on how they influence the esthetic perception of the facial profile.…”
Section: Discussionmentioning
confidence: 99%